Design And Development Of A Flight Operator Safety Audit System - Yee, Qian Hui (Universiti Sains Malaysia, 2022)
Industry 4.0 is defined as the integration between machines and digital technologies to control, predict and planning for business. One of the enablers of Industry 4.0 is the digitalization of business due to digital technologies such as Cloud Computing and Big Data and Analytics. Safety, on the other hand, is a critical component in the aviation sector, as the majority of flight mishaps are fatal. Line Operation Safety Audit (LOSA) is one of The LOSA Collaborative's (TLC) proactive safety management solutions based on Threat and Error Management (TEM) to acquire and evaluate human behavior data during normal operations and next product countermeasures before occurrence. Using prior LOSA experiences, Malaysia Airlines Berhad (MAB) chose to launch a safety audit program called Flight Operation Safety Audit (FOSA) and work with Universiti Sains Malaysia (USM) to design a framework for the program. This study focuses on the design and implementation of a user-friendly and secure system that collects, saves, and analyzes FOSA data utilizing Microsoft business engineering applications such as Microsoft Excel and Microsoft Access.